Estudio jurídico del despido intempestivo en el ecuador y las bajas indemnizaciones previstas en el código de trabajo - Estrada Dávila, Rosita Virginia (2017)
The Constitution of the Republic of Ecuador in Art. 33 recognizes us and guarantees the right to work to all Ecuadorians. The work is one of the most important rights of each and every one of us, because through it gives us a compensation and therefore one way or another to improve the quality of life of workers and their families regardless of the amount of remuneration. Likewise, work a number of benefits for workers generally become, like Social Security, among others. The work is much more productive when there is a real stability to the worker; however, this stability is affected when the Labour Code, specifically in Art. 188 still continue to set very soft or low compensation that make everyday an employer to dismiss a worker unexpectedly. The problem of dismissal is very serious and brings a series of injuries for workers and their families, such as unemployment, poverty, lack of social security, psychosocial problems at work, ie a number of drawbacks which can not easily remedied and that leaves many sequels. If there are higher compensation in case of unfair dismissal on the one hand it would ensure genuine stability for workers and abuse of many employers who prefer to pay current compensation provided to keep workers in their offices or jobs would be avoided. In the latest reforms introduced to the Labour Code in April of this year through the Organic Law for Labor Justice and Labor Award at Home, progress was made in some the figure of ineffective dismissal was created in the case of pregnant women, however the biggest problem remains latent in the case of other workers, and allowances provided have not changed and they allow that the rights of workers are violated, such as the right their job security.